THE USE OF HORSERADISH IN FOOD AND MEDICINE IN THE NORDIC COUNTRIES - Bladh, K. W.; Olsson, K.; Asdal, A.; Brantestam, A. K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Horseradish, Armoracia rusticana P. Gaertn., B. Mey. & Scherb. has a long history as a plant used by man and it was already mentioned in “De material medicia libri quinque” written in 100 A. D. The plant, which has its origin in southeast Europe, was brought to the Nordic countries by monks during the thirteenth century. In the Nordic countries, horseradish was used both as a bitter spice and as a medicinal plant. The plant contains high levels of sulfur-containing glycosides, so called glucosinolates. The most dominant is sinigrin, which causes a pungent taste . Some glucosinolates also possess anti-microbial characters, and horseradish has traditionally been used as a component in preserving. The root also has a high content of vitamin C and was taken to prevent scurvy on long sailing tours. Horseradish was also used as a medicinal plant for headaches, digestive disorders, high blood pressure and gout. Earlier it was also believed that the plant had magical powers and could prevent snakebites if you had rubbed your hands with it. The production of horseradish has decreased in the Nordic countries due to high production costs, changes in traditional cooking manners and a decrease in homemade preserving. NordGen, the Gene Bank for the Nordic countries, has a collection of horseradish consisting of 170 accessions. The roots were collected from old gardens or as refugees from gardens in Denmark, Finland, Norway and Sweden. The accessions have been evaluated for contents of glucosinolates and vitamin C and a large variation in bioactive substances has been found .